An ERP study on verb bias and thematic role assignment in standard Indonesian - Bernard A. J. Jap; Yu-Yin Hsu (Scientific Reports)
Abstract This study investigates the effects of verb bias on sentence comprehension in Standard Indonesian (SI), a language where the passive construction is frequent and salient. We examined the hypothesis that lexical biases influence processing efforts. To disentangle effects of verb bias from structural effects, we held structure constant by using only passive sentences in our event-related potential (ERPs) experiment. Using an SI corpus, we identified verbs more frequently used in passive sentences (“passive-bias verbs”) and those more frequently used in active ones (“active-bias verbs”) to form passive sentences. Cluster-based permutation tests revealed significant differences between conditions. In the postverbal region (adverb), passive sentences with active-bias verbs elicited a broadly distributed negative shift that corresponded to the N280 distribution, a component associated with grammatical processing complexity. This suggests that active-bias verbs in passive contexts impose greater processing demands than their passive-bias counterparts, reflecting the integration of verb-specific preferences with sentence structure. These findings highlight how verb bias influences sentence comprehension and provide insights into cross-linguistic differences. In languages with predominantly active-bias verbs, using them in passive constructions may amplify processing costs. This study shows the importance of lexical biases and structural preferences in shaping sentence processing, contributing to a broader understanding of the interaction between lexical and syntactic factors in language comprehension.